Strategi Pengembangan Agroindustri Keripik Kulit Ikan Patin (Studi Kasus pada Rafin’s Snack Kabupaten Pringsewu) - Nismara, Anindya Putri; Haryono, Dwi; Affandi, Muhammad Irfan (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
This study aims to analyze the development strategy of Pangasius skin chips agroindustry. The location of this research was determined with consideration of Rafin’s Snack is the largest chip agroindustry in Pajaresuk District and yet still has the potential to be developed. Respondents in this study consisted of various parties involved to the analysis of development strategy for the agroindustry, namely agroindustry owners, representatives of the Pringsewu District Fisheries Service, the Office of Cooperatives, SMEs, Industry and Trade of Pringsewu District, and a lecturer at the University of Lampung. Data was collected in January 2023. The analytical method used was SWOT analysis (Strength, Weakness, Opportunity, Threat) and QSPM (Quantitative Strategic Planning Matrix) analysis. The results showed that the main strength of Rafin’s Snack Agroindustry is the availability of sufficient raw materials, the main weakness is limited capital, the main opportunity is wide market reach, the main threat is the change in people’s tastes. The prioritized development strategies for Rafin’s Snack Agroindustry are to do consumer research and to adapt by creating more flavors to the product, to use a cloud-based cashier application (point of sale) in making transactions, to use electronic word of mouth (eWOM) by using the services of influencers or key opinion leaders (KOL) for promoting product and improving brand awareness, to organize educational seminars in collaboration with universities (business goes to campus) to strengthen brand identity and build consumer trust, as well as to utilize production machine provided by the Pringsewu District Fisheries Service.